A Non-Fourier Bioheat Transfer Model for Cryosurgery of Tumor Tissue with Minimum Collateral Damage. (March 2021) - Barman, C.; Rath, P.; Bhattacharya, A.
Highlights: A non-Fourier Bioheat transfer model is proposed for modeling cryosurgery of tumor tissue. The proposed numerical model is developed on the framework of Fourier heat conduction based Solver. Laser heating surrounding the tumor tissue reduces the collateral damage of the healthy tissue. Step increase in laser power with narrow exposure area is more effective in confining the frozen tissue within the tumor region. Abstract: Background and objectives: Incorporation of non-Fourier heat conduction while studying heat transfer phenomena in biological materials has emerged has an important approach as it predicts better and more realistic results than Fourier based models. In this article we have proposed a non-Fourier computational model and applied the same to simulate cryosurgery of lung tumor and attempted minimization of freezing damage of healthy lung tissue using pulsed laser irradiation. Methods: A non-Fourier bioheat transfer model for phase change in biological tissues is solved via a Fourier heat conduction based solution approach. A unified model is proposed combining all variants of bioheat models: Fourier's heat conduction based Pennes' bioheat model, hyperbolic heat conduction model and dual phase lag model. The proposed model takes into account the different thermophysical properties of frozen and unfrozen regions. In order to mimic the actual biotransport process, the blood perfusion and metabolic heat generation are switched off in the frozen region. Implicit source based enthalpy method is used to model phase change process. A new iterative enthalpy update equation is developed for capturing evolution of freezing front implicitly. Finite Volume based numerical discretization technique is used to discretize the governing PDE. The resulting discrete algebraic equation set is solved implicitly by Tri-diagonal Matrix Algorithm. The proposed model is verified with existing results from the literature. Results: For Fourier heat conduction, freezing time of 99.99% of tumor is 1247s, which increases to 1267s for τ q = 5s (τ T = 0s) and again reduces to 1255s for τ q = 5s and τ T = 3s. τ q and τ T are phase lag parameters for non-Fourier heat conduction. For τ q = 5s and τ T = 0.05s, the freezing damage of healthy tissue decreases by 23.76% when pulsed laser irradiation ( Io = 10 6 W/m 2 ) is used to warm the neighboring healthy tissue. Conclusions: So non-Fourier bioheat transport models are better and more accurate in predicting temperature history, freezing time and freezing front propagation as compared to Fourier based models. Pulsed laser irradiation can prove to be a very efficient technique in minimizing collateral damage during cryosurgery.